Metal ion-crosslinking multifunctional hydrogel microspheres with inflammatory immune regulation for cartilage regeneration - Xu, Zhuoming; Ma, Jun; Hu, Hanyin; Liu, Jintao; Yang, Haiyang; Chen, Jiayi; Xu, Hongwei; Wang, Xinyu; Luo, Huanhuan; Chen, Gang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionOsteoarthritis (OA) is a degenerative disease of the joints characterized by cartilage degradation and synovial inflammation. Due to the complex pathogenesis of OA, multifaceted therapies that modulate inflammatory and immune microenvironmental disturbances while promoting cartilage regeneration are key to control the progression of OA.MethodsHerein, a multifunctional nanoparticle (DIC/Mg-PDA NPs) was constructed successfully by the metal chelation effect between Mg2+ and catecholamine bond from dopamine, followed by the amidation with diclofenac (DIC), which was then prepared into an injectable hydrogel microsphere (DIC/Mg-PDA@HM) with immune-regulating and cartilage-repairing abilities through microfluidic technology for the treatment of osteoarthritis.Results and discussionThe sustained release of Mg2+ from the composite hydrogel microspheres achieved inflammatory immune regulation by converting macrophages from M1 to M2 and promoted cartilage regeneration through the differentiation of BMSCs. Moreover, the enhanced release of DIC and polydopamine (PDA) effectively downregulated inflammatory factors, and finally achieved OA therapy. In addition, in vivo MRI and tissue section staining of OA model proved the significant efficacy of the hydrogel microspheres on OA. In conclusion, these novel hydrogel microspheres demonstrated a promising prospect for multidisciplinary repairing of OA.